RETROSPECTIVE ANALYSIS OF THE PRIORITY FACTOR IN THE MOBILIXATION POLLUTANTS - Shevchenko, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Efficiency of methodological approach is shown on creation of empiric regressive models of concentration forming and annual subtraction of сontaminant. A model consists of independent parameters, characterizing of drainage area and determining the degree of the second radio contaminant of surface-stream flows.